Perception and attitude of mothers toward family planning in Southern Nigeria - Inyang-Etoh, Emmanuel Columba; Abah, Matthias Gabrie l (Family Medicine & Primary Care Review, 2017)
Background . The prevailing low utilization of modern contraceptives for family planning in developing countries in spite of an almost universal level of awareness by the populace is a cause for concern by relevant stakeholders. Objectives. The aim of this study was to determine the feeling and attitude of women toward family planning and the reasons for such attitude. Material and methods . A 7-item structured, pre-coded questionnaire was used to sample respondents’ feelings and attitude toward family planning. Results. All the respondents were aware of family planning, and 412 (90.9%) of them believed in the practice. The majority 269 (59.4%) of the respondents preferred to allow 24 months between their last delivery and the next pregnancy. 306 (74.3%) respondents believed in the use of modern contraceptives for family planning and preferred: the male condom – 160 (52.3%), intrauterine contraceptive device (IUCD) – 27 (8.8%), and hormonal contraceptives – 119 (38.9%). Those who did not believe in modern contraception preferred abstinence – 12 (11.3%), the withdrawal technique – 75, (70.8%) and the rhythm method – 19 (17.9%). The major reasons why some respondents would not use modern contraceptives for child spacing were the feeling that it is not natural - 39 (36.6%), it could fail – 13 (12.2%), fear of side effects – 41 (39.0%), and the fear that it could cause infertility – 13 (12.2%). Conclusions . The willingness to utilize modern contraceptives for family planning in Nigeria remains relatively low despite a universal level of awareness about the practice. This is due to misconceptions about modern contraception.